2008
DOI: 10.1029/2008ja013494
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of ring current H+ in electromagnetic ion cyclotron wave dispersion relation: Results from global simulations

Abstract: [1] The effect of ring current (RC) H + in the real part of electromagnetic ion cyclotron (EMIC) wave dispersion relation is studied on the global magnetospheric scale. The simulations of the 2-3 May 1998 storm are done using our model of the He + -mode EMIC waves self-consistently interacting with RC ions. The wave model describes EMIC waves bouncing between the off-equatorial magnetic latitudes, which correspond to the bi-ion hybrid frequencies in conjugate hemispheres, along with tunneling across the reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…In the present study, we also included the RC H + and O + only in the imaginary part of the EMIC wave dispersion relation but neglected it in the real part. (The effect of RC H + in the real part of wave dispersion relation was previously discussed, for example, by Gamayunov and Khazanov [2008].) As follows from Figure 3 in the paper by Gamayunov et al [2009], the cross polar cap potential (CPCP) drop grows from about 50 kV up to about 275 kV during approximately 2 h from 74 to 76.…”
Section: Appendix A: Distributions Of Plasmaspheric Density and Rc Pamentioning
confidence: 81%
“…In the present study, we also included the RC H + and O + only in the imaginary part of the EMIC wave dispersion relation but neglected it in the real part. (The effect of RC H + in the real part of wave dispersion relation was previously discussed, for example, by Gamayunov and Khazanov [2008].) As follows from Figure 3 in the paper by Gamayunov et al [2009], the cross polar cap potential (CPCP) drop grows from about 50 kV up to about 275 kV during approximately 2 h from 74 to 76.…”
Section: Appendix A: Distributions Of Plasmaspheric Density and Rc Pamentioning
confidence: 81%
“…The second model is governed by a coupled system of the RC kinetic equation and the wave kinetic equation. This model self‐consistently treats a mesoscale electrodynamic coupling of RC and EMIC waves, and determines the evolution of the EMIC wave power spectral density [ Gamayunov and Khazanov , 2008]. The RC‐EMIC wave model explicitly includes the wave growth/damping, propagation, refraction, reflection, and tunneling in a multi‐ion magnetospheric plasma.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the main purpose of this paper is to present a new self‐consistent model of the magnetospheric electric field, RC, plasmasphere, and EMIC waves along with initial results from the model simulations. The results presented in this study were obtained from simulations of the 2–4 May 1998 geomagnetic storm, that we previously analyzed using an analytical formulation of the Volland‐Stern electric field [ Khazanov et al , 2006, 2007b; Gamayunov and Khazanov , 2008].…”
Section: Introductionmentioning
confidence: 99%
“…In a hydrogen plasma there is one frequency band (hydrogen band) where waves can be observed, while in a multi-ion plasma EMIC waves are observed in three separate bands. A number of modeling studies explored the role of H + , He + , and O + ions on the excitation and propagation properties of EMIC waves (e.g., Gamayunov and Khazanov 2008;Omidi et al 2013, and references therein). Omidi et al (2013) using hybrid simulations (kinetic for ions and fluid for electrons) showed that EMIC waves are generated in the near equatorial region and propagate parallel or anti-parallel to the magnetic field directly towards the ionosphere where they are absorbed when the O + concentration is lower than 7 %.…”
Section: Electromagnetic Ion Cyclotron Wavesmentioning
confidence: 99%